Automotive supply chain networks equilibrium model under uncertain payment delay and objective weights. (December 2020) - Chen, Jiajia; Xu, Zeshui; Huang, Dongbin; Fang, Changjie; Wang, Xinxin; Zhang, Jianchuan
Graphical abstract: Highlights: Payment delay choices are studied in the network equilibrium model of an automotive supply chain. Adjusting procedures are devised to result in a converged equilibrium price for automotive parts. Payment delay impacts on the equilibrium volume and price in both electronic and draft transaction modes. Payment delay proposals are yielded by maximizing the profits at equilibrium states of the network. Abstract: Supply chain network equilibrium has become an important issue for most manufacturing enterprises, especially for the automotive industry. This paper proposes an equilibrium model for analyzing a three-tier automotive supply chain network under uncertain payment delay, in which parts manufacturers and automobile manufacturers are both multi-objective decision makers (DMs). Their rationality under payment delay are elaborated as to maximize business income and to minimize costs, and the equilibrium conditions of the network are formulated as a finite-dimensional variational inequality problem. To solve the model, we analyze the properties of the variational inequality and prove the solvability of the problem, i.e., the existence of solutions, and in turn apply convergent algorithm to reach a solution of equilibrium state at each possible payment delay scenarios. The equilibrium state that has the maximal profit is chosen as a solution, including transaction volume, price, profit distribution and payment delay strategies. By applying the model in a case of Chongqing SOKON Co. Ltd. China, we showcase the processes of finding the equilibrium state with payment delay for its supply chain networks; and how payment delay affects the equilibrium states in both electronic transaction mode and draft transaction mode. Results show that the model informs on equilibrium state and payment delay strategies choice that are compatible to the interests of network members.